A review of the exclusion technique as a mode of surgical repair in the treatment of aortoiliac aneurysms with spontaneous arteriovenous fistulas - Kiziltan, Hidayet Tarik (Forum Multimedia Publishing LLC, 2018)
Patients with aortoiliac aneurysms with arteriovenous fistulas are difficult to treat. The traditional mode of surgical repair using aneurysmal excision, fistula closure, and graft inclusion has been associated with high perioperative mortality. As an alternative, the exclusion technique also has been utilized. Over the years, the popularity and success rate of endovascular techniques have increased in the treatment of these patients, yet a technical failure during an endovascular repair always makes surgical repair inevitable. This paper aims to review the outcomes of aneurysmal exclusion as a modality of surgical repair in the treatment of patients with aortic and/ or iliac aneurysms with arteriovenous fistulas. The literature in English was researched utilizing the MEDLINE database. Articles reporting on surgical exclusion of abdominal arterial aneurysms with arteriovenous fistulas were included. Overall, four cases in three patients and our unpublished experience in a fifth case were evaluated. There were two aortoiliac, one aortic, one secondary iliac, and one pure iliac artery aneurysm, all with fistulas into the venous system. All patients recovered well following the exclusion operations. There were no operative or 30-day mortalities. One patient had inferior vena cava obstruction. Another patient developed a secondary iliac artery aneurysm with iliac vein fistula two years postoperatively, due to an internal iliac artery, which was not ligated during the first operation. Reported data indicates that for patients who have aortoiliac aneurysms with arteriovenous fistulas, the exclusion technique is a viable surgical alternative either as a first-line choice or when other strategies are technically not feasible.
Keywords: adult; aged; aneurysm surgery; aortic aneurysm; aortoiliac aneurysm; arteriovenous fistula; Article; case report; clinical article